2022
DOI: 10.3847/1538-4357/ac7562
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Peas in a Pod: Extending Intra-system Mass Uniformity to Non-TTV Systems via the Gini Index

Abstract: It has been demonstrated that planets belonging to the same close-in, compact multiple-planet system tend to exhibit a striking degree of uniformity in their sizes. A similar trend has also been found to hold for the masses of such planets, but considerations of such intra-system mass uniformity have generally been limited to statistical samples wherein a majority of systems have constituent planetary mass measurements obtained via analysis of transit timing variations (TTVs). Since systems with strong TTV sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…The occurrence rate of these giant planets increases as a function of the amount of solid material in the disk (which is itself correlated to the mass and metallicity of the host star, Fischer & Valenti 2005, as well as the formation location within the protoplanetary disk; Wittenmyer et al 2020;Fulton et al 2021). This starting point is, in part, motivated by the prevalence of "peas-in-a-pod" chains of super-Earths and sub-Neptunes discovered in the Kepler data set (Millholland et al 2017;Weiss et al 2018;Goyal & Wang 2022), as well as the existence of Jovian planets observed in some compact multiplanet systems (see Wang et al 2017;Adams et al 2020, and Figure 1 of Dawson et al 2019). More importantly, however, we find that a framework based on this initialization is able to qualitatively reproduce the observed properties of hot and warm Jupiters, as is further discussed in Section 7.4.…”
Section: Framework Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence rate of these giant planets increases as a function of the amount of solid material in the disk (which is itself correlated to the mass and metallicity of the host star, Fischer & Valenti 2005, as well as the formation location within the protoplanetary disk; Wittenmyer et al 2020;Fulton et al 2021). This starting point is, in part, motivated by the prevalence of "peas-in-a-pod" chains of super-Earths and sub-Neptunes discovered in the Kepler data set (Millholland et al 2017;Weiss et al 2018;Goyal & Wang 2022), as well as the existence of Jovian planets observed in some compact multiplanet systems (see Wang et al 2017;Adams et al 2020, and Figure 1 of Dawson et al 2019). More importantly, however, we find that a framework based on this initialization is able to qualitatively reproduce the observed properties of hot and warm Jupiters, as is further discussed in Section 7.4.…”
Section: Framework Overviewmentioning
confidence: 99%
“…The occurrence rate of these giant planets increases as a function of the amount of solid material in the disk (which is itself correlated to the mass and metallicity of the host star Johnson et al 2010), as well as the formation location within the protoplanetary disk (Wittenmyer et al 2020;Fulton et al 2021)). This starting point is, in part, motivated by the prevalence of "peas-in-a-pod" chains of super-Earths and sub-Neptunes discovered in the Kepler dataset (Millholland et al 2017;Weiss et al 2018;Goyal & Wang 2022), as well as the existence of Jovian Expected # of Jupiters with detected transiting companions…”
Section: Framework Overviewmentioning
confidence: 99%
“…Previous studies of multiplanet systems have revealed that planets within the same system tend to have similar radii, orbital spacings (Weiss et al 2018b), and masses (Millholland et al 2017;Goyal & Wang 2022), such that they are like "peas in a pod". Put another way, planets within the same system have similar bulk densities.…”
Section: Planetary Core/water Mass Fractionsmentioning
confidence: 99%
“…Following the methodology of Goyal & Wang (2022), we adopt the adjusted Gini index (Gini 1912;Deltas 2003), a statistic commonly used in economics to quantify income or wealth inequality in a given population, as our primary metric for the assessment of intra-system size uniformity across our sample. For a given data vector x with size N, the standard Gini index can be calculated as follows:…”
Section: Gini Indexmentioning
confidence: 99%
“…The extension of peas-in-a-pod uniformity to planetary mass, however, necessitates consideration of orbital resonances due to the distinct observational means (Lithwick & Wu 2012) by which mass measurements may be obtained for systems near or distant from mean motion resonance (MMR): individual transiting planets in a nonresonant system may have their masses constrained by radial velocity (RV) follow-up (Batalha et al 2011;Weiss & Marcy 2014), while planet pairs whose orbits lie near MMR may have their masses determined instead via analysis of their transit timing variations (TTVs; Lithwick & Wu 2012;Steffen et al 2012;Xie 2013;Hadden & Lithwick 2017). Nonetheless, intra-system mass uniformity has been demonstrated independently for near-resonant systems exhibiting strong TTVs (Millholland et al 2017), predominantly nonresonant systems with RV masses (Goyal & Wang 2022), a mixed sample of both system types (Wang 2017;Otegi et al 2022), thereby suggesting that the emergence of peas-in-a-pod regularity persists regardless of proximity to MMR.…”
Section: Introductionmentioning
confidence: 99%